Functional skewing of TRIM21‐SIRT5 interplay dictates IL‐1β production in DSS‐induced colitis. (30th June 2022) - Yao, Pengbo; Chen, Taiqi; Jiang, Peng; Li, Li; Du, Wenjing
Abstract: Macrophage polarization determines the production of pro‐ or anti‐inflammatory cytokines in response to various bacterial and virus infections. Here, we report that pro‐inflammatory macrophage polarization induced by lipopolysaccharide (LPS) skews the TRIM21‐SIRT5 interplay toward TRIM21 activation and SIRT5 degradation, resulting in an enhancement of interleukin (IL)‐1β production in vitro and in vivo . Mechanistically, LPS challenge enhances the interaction between TRIM21 and SIRT5 to promote SIRT5 ubiquitination and degradation, while reducing the binding of SIRT5 to HAUSP, a deubiquitinating enzyme that stabilizes SIRT5. In a feedback loop, SIRT5 degradation sustains the acetylation of TRIM21 at Lys351, thereby increasing its E3 ligase activity in LPS‐activated macrophages. Thus, we identify a functional balance between TRIM21 and SIRT5 that is tilted toward SIRT5 suppression in response to LPS stimulation, thereby enhancing IL‐1β production during inflammation. Synopsis: The competitive binding of the E3 ligase TRIM21 and the DUB HAUSP is skewed in favor of TRIM21 upon LPS stimulation, resulting in SIRT5 degradation and enhanced pro‐inflammatory cytokine production in macrophages. The E3 ubiquitin ligase TRIM21 directly binds to and promotes SIRT5 degradation through K48‐linked ubiquitination. SIRT5 suppresses TRIM21 E3 ligase activity through deacetylating TRIM21 at Lys351 HAUSP competes with TRIM21 to interact with SIRT5, thereby stabilizing SIRT5. In LPS‐activated macrophages, SIRT5 is prone to form a complex with TRIM21, but not HAUSP, which leads to SIRT5 degradation and IL‐1β production. SIRT5 knockout aggravates DSS‐induced colitis in mice, while knockout of TRIM21 in SIRT5‐deficient mice protects against colitis. Abstract : The competitive binding of the E3 ligase TRIM21 and the DUB HAUSP is skewed in favor of TRIM21 upon LPS stimulation, resulting in SIRT5 degradation and enhanced pro‐inflammatory cytokine production in macrophages.